EDUCATION AND THERAPY OF SALAM LEAVE BOILED WATER FOR PATIENTS WITH HYPERTENSION: Edukasi Dan Terapi Air Rebusan Daun Salam Untuk Penderita Hipertensi - Setyaningrum, Niken; Suryati; Darmawan, Ardhian Indra (Jurnal Pengabdian Masyarakat Kesehatan Terkini, 2024)
Hypertension is a health problem that causes early death. Hypertension or high blood pressure is a condition where there is an increase in blood pressure above the normal threshold, which is above 120/80 mmHg. A healthy lifestyle is needed to be able to control blood pressure, apart from taking hypertension drugs. One way to prevent hypertension is through non-pharmacological therapy, namely salam leaf oiled water. Name of Activity: This community service activity is an education and demonstration of making salam leaf boiled water for hypertensive sufferers. Activity Objectives: Increase knowledge of lifestyle and non-pharmacological therapy for people with hypertension. Implementation Method: The implementation of this community service was carried out in 3 sessions, namely: session 1. About education on healthy lifestyles for people with hypertension; session 2. Demonstration of boiled bay leaves; session 3. Evaluation. Conclusion of the activity: Based on the results of the posttest there was an increase in scores related to the level of knowledge of healthy lifestyles in people with hypertension, participants actively discussed with questions and answers after the material was delivered. The demonstration of boiled salam leaves can be carried out by participants and some participants drink the boiled water of salam leaves. Suggestion: After education and demonstration of making bay leaf boiled water, it is hoped that it can increase knowledge and be able to control blood pressure in hypertensive patients with non-pharmacological therapy.